Organization of the learning process by means of Google Drive at the IT-Academy Vinnytsia - Ya. I. Plaksii (Academy of Cognitive and Natural Sciences, 2013)
The organization of the educational process in Ukraine today requires both speed and quality. The educational process at the  IT-Academy Vinnytsia implies the use of Google Docs in the learning process, completely replacing paper data carriers. For example, in order to effectively conduct interviews, future students are invited to fill out a Google Docs form, the entrance to which is on the website of the institution. Once an applicant fills out the form, he or she is scheduled for an interview. After enrollment, each student gets access to a personal folder, which is located on Google Drive, where they will store their completed homework and other materials related to the learning process.